Combined strengthening mechanism of solid-state bonding and mechanical interlocking in friction self-piercing riveted AA7075-T6 aluminum alloy joints. (10th April 2022) - Ma, Yunwu; Yang, Bingxin; Hu, Shanqing; Shan, He; Geng, Peihao; Li, Yongbing; Ma, Ninshu
Highlights: Solid-state and dual-interlocking hybrid joining of AA7075-T6 is realized by friction self-piercing riveting. Rivet stirring causes both continuous and discontinuous dynamic recrystallization, contributing to a sound solid-state bonding. Solid-state bonding zone exhibits 81% ultimate tensile strength and 106% elongation compared to base metal. The solid-state bonding contributes to a 14.3% increment in cross-tension peak force compared to pure mechanically fastened joint. Abstract: A recently developed friction self-piercing riveting (F-SPR) technique based on the combination of friction stir processing and riveting has been reported to possess both solid-state bonding and mechanical fastening characteristics. However, there is still a lack of quantitative understanding of the hybrid enhancement mechanism, hindering its engineering application. To fill in this gap, the current research investigated the microstructure evolution, microhardness distribution, and miniature-tensile performance of the aluminum alloy AA7075-T6 F-SPR joints by experiments. An accurate numerical simulation model was established to quantitatively evaluate the individual contributions of microstructure, local bonding strength, and macro interlocking to the performance of the joint, which could well explain the experimental results. It was found that due to the friction stirring of the rivet, solid-state bonding driven by dynamic recrystallization is realized between the trapped aluminum in the rivet cavity and the bottom aluminum sheet. The solid-state bonding zone has 75% yield strength, 81% ultimate tensile strength, and 106% elongation compared to the base material. This solid-state bonding enables the internal interlocking between the trapped aluminum and the rivet to withstand the additional load, which forms a novel dual-interlock fastening mechanism and increases the peak cross-tension force by 14.3% compared to the single-interlock joint. Abstract : Image, graphical abstract